Adherence to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist in articles published in EAACI Journals: A bibliographic study. Issue 12 (28th November 2021) - Wiehn, Elena; Ricci, Cristian; Alvarez‐Perea, Alberto; Perkin, Michael R.; Jones, Christina J.; Akdis, Cezmi; Bousquet, Jean; Eigenmann, Philippe; Grattan, Clive; Apfelbacher, Christian J.; Genuneit, Jon; ,
Abstract: Research data derived from observational studies are accumulating quickly in the field of allergy and immunology and a large amount of observational studies are published every year. The aim of the present study was to evaluate the adherence to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist by papers published in the three European Academy of Allergy and Clinical Immunology journals, during the period 2009–2018. To this end, we conducted a bibliographic study of up to eight randomly selected papers per year per Journal. Our literature search resulted in 223 papers. Amongst those, 80, 80 and 63 records were from Paediatric Allergy and Immunology, Allergy and Clinical and Translational Allergy, respectively; the latter was published only from 2011 on. Prospective, case control and cross‐sectional designs were described in 88, 43 and 92 papers, respectively. Full reporting of all STROBE items was present in 47.4%, 45.6% and 41.2% for the cohort, cross‐sectional and case‐control studies, respectively. Generally, no time trend in adherence of reporting STROBE items was observed, apart from reporting funding, which increased from 60% in 2009/2010 to more than 90% in 2018. We identified a cluster of STROBE items with low proportions of full reporting constituted by the items on reporting study design in the title and methods, variables types along with their measurement/assessment, bias and confounding, study size, and grouping of variables. It appears that the STROBE checklist is a suitable tool in observational allergy epidemiology. However, adherence to the STROBE checklist appeared suboptimal. Abstract :